DURABILITY PROPERTIES OF CONCRETE MADE WITH RECYCLED CONCRETE AGGREGATE AND METAKAOLIN AS CEMENT REPLACEMENT - Abiola, O. S.; Sulaimon, B. A.; Odunfa, S. O. (Academy Journal of Science and Engineering)
Production of concrete with recycled concrete aggregates (RCA) in civil infrastructure is growing and the quest for durable concrete in aggressive environment has placed demands for use of supplementary cementitious materials as replacement for cement. This paper present research on the durability of RCA in concrete pavement and metakaolin (MK) as partial replacement of cement. Five mix designs were produced with a targeted strength of 45 N/mm2 at 28 day test. These were designated as C0, MK10, MK20, MK30 and MK40 with water-cement ratio of 0.4. Compressive strength tests were performed at 28, 56 and 90 days. While durability was evaluated through chloride, sulphate resistance attack and water absorption tests according to BS EN 1338: 2003 specification. Results of water absorption test showed that all the mixes met the specification (< 6%) though C0 has the highest value. Cement-MK blends concrete in chloride and sulphate solution have the least loss in strength and mass compared to the control (C0). The compressive strength losses in sulphate solution of MK10, MK20, MK30 and MK40 at 28th day were 4.47, 5.55, 5.07 and 6.42% respectively.